Exploring palatal dimensions in a sample of kurdish edentulous population: influence of age, gender and duration of edentulism - Neda AL-Kaisy; Jwan F Abdulkareem; Lazyan L Raouf; Hawa M Fathi (Journal of Baghdad College of Dentistry)
Background: Complete denture construction requires accurate measurements of the edentulous palate to ensure optimal fit and function. This study aimed to evaluate palatal dimensions in a sample of Kurdish edentulous population and determine the effects of age, gender and duration of edentulism on these measurements. Materials and Methods: Maxillary stone models were obtained from 51 edentulous participants, comprising 26 women and 25 men aged 40–75 years. Palatal linear measurements, including length, width and height, along with ratios involving palatal, rugae, and incisive papilla area size, were evaluated and correlated with age, sex and the edentulous duration. Digital caliber and ImageJ software were employed for accurate linear measurements and size evaluations. Results: A significant sex-related impact was found on the palatal size in middle palate width and posterior height, with men exhibiting higher values than women (45.29 and 12.47 mm vs. 43.2 and 10.78 mm). Palatal ratios remained consistent across both sexes. Notably, an increase in palatal height was observed with longer durations of edentulism (H1–H3 increased from 6.68, 10.42 and 10.07 mm, respectively, to 8.30, 12.72 and 12.87 mm, respectively). Conclusions: Men demonstrated significantly higher values in middle palatal width, posterior height and palate area size than women. This study underscores the influence of age and edentulous duration on palatal dimensions, providing valuable data to guide clinicians in their dental rehabilitation planning. Palatal height indices were identified as a valuable tool for exploring denture construction.